Hands-on neural networks learn how to build and train your first neural network model using Python - De Marchi, Leonardo (Packt Publishing, 2019)
This book will be a journey for beginners who want to step into the world of deep learning and artificial intelligence. It will thoughtfully take you through the training and implementation of various neural network architectures using the Python ecosystem. You will master each neural network architecture while understanding its working mechanism.